2022
DOI: 10.3390/ani12111459
|View full text |Cite
|
Sign up to set email alerts
|

First Description of Serological Evidence for SARS-CoV-2 in Lactating Cows

Abstract: Following the COVID-19 epidemic outbreak in Ariano Irpino, Campania region (Italy), we tested lactating cows for the presence of SARS-CoV-2 on a cattle farm at which, prior to the investigation, 13 of the 20 farmworkers showed COVID-19-like symptoms, and one of them died. Twenty-four lactating cows were sampled to detect SARS-CoV-2. All nasal and rectal swabs and milk samples were negative for SARS-CoV-2 RNA. Of the 24 collected serum samples, 11 showed antibodies against SARS-CoV-2 nucleocapsid protein, 14 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…org/licenses/by/4.0/. other highly sensitive animal species, such as minks, cats and dogs and for lower susceptible species, as cattle (Fiorito et al, 2022). Albeit, our results showed that only the 38.4% of the positive herds referred a case of human COVID-19, thus opening the question about further sources of infection for these animals, probably through the environment.…”
Section: Declarationsmentioning
confidence: 52%
See 3 more Smart Citations
“…org/licenses/by/4.0/. other highly sensitive animal species, such as minks, cats and dogs and for lower susceptible species, as cattle (Fiorito et al, 2022). Albeit, our results showed that only the 38.4% of the positive herds referred a case of human COVID-19, thus opening the question about further sources of infection for these animals, probably through the environment.…”
Section: Declarationsmentioning
confidence: 52%
“…In particular, inter-species transmission from humans to animals or intra-species within the flock are not easy to explore. It can be supposed that in areas with large population of small ruminants, associated with the presence of SARS-CoV-2 infection in humans, close contact between livestock and farmworkers may have caused a reverse zoonotic infection as hypothesized for other highly sensitive animal species, such as minks, cats and dogs and for lower susceptible species, as cattle (Fiorito et al, 2022 ). Albeit, our results showed that only the 38.4% of the positive herds referred a case of human COVID-19, thus opening the question about further sources of infection for these animals, probably through the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the study also found limited seroconversion and no clear evidence of transmission to sentinel calves[18]. A study in 2022 reported detection of SARS-CoV-2 antibodies in lactating cows in Italy[19]. Subsequently, a serological survey in Germany found antibody evidence of natural SARS-CoV-2 exposure of cattle[20].…”
Section: Introductionmentioning
confidence: 99%